Evaluation of the UFXC32k photon‐counting detector for pump–probe experiments using synchrotron radiation. (21st February 2018) - Koziol, Anna; Bordessoule, Michel; Ciavardini, Alessandra; Dawiec, Arkadiusz; Da Silva, Paulo; Desjardins, Kewin; Grybos, Pawel; Kanoute, Brahim; Laulhe, Claire; Maj, Piotr; Menneglier, Claude; Mercere, Pascal; et al.
Abstract : The performance of a new hybrid pixel detector is assessed with the aim of providing a single‐photon‐counting imager for time‐resolved experiments presently under preparation at Synchrotron SOLEIL. Abstract : This paper presents the performance of a single‐photon‐counting hybrid pixel X‐ray detector with synchrotron radiation. The camera was evaluated with respect to time‐resolved experiments, namely pump–probe–probe experiments held at SOLEIL. The UFXC camera shows very good energy resolution of around 1.5 keV and allows the minimum threshold setting to be as low as 3 keV keeping the high‐count‐rate capabilities. Measurements of a synchrotron characteristic filling mode prove the proper separation of an isolated bunch of photons and the usability of the detector in time‐resolved experiments.